'In all my years of experience working in the renal charity sector, I have never seen such levels of poverty, hardship, anxiety and distress'. (2nd January 2023) - MBE, Sandy Lines
Abstract : Sandy Lines MBE discusses the latest in the 'cost of staying alive' crisis